Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Canva Site terhadap Kemampuan Berpikir Spasial Siswa - Ariska Candra Jayati (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to analyze the effect of the application of the Problem-Based Learning (PBL) learning model assisted by Canva Site media on the spatial thinking skills of high school students. The background of this study is the low ability of students to understand the relationship between geosphere phenomena in depth, which is caused by the lack of application of learning methods that stimulate spatial thinking skills. Spatial thinking is an essential skill in geography learning that includes the ability to understand relationships, patterns, and spatial processes in the surrounding environment. Therefore, an innovative learning approach is needed that can improve these skills. The research method used is a quasi-experimental with a posttest only control design. The research subjects consisted of two classes, namely the experimental class that applied the PBL model assisted by Canva Site media and the control class that used the PBL model assisted by PowerPoint media. The research instrument included posttest questions in the form of descriptions designed to measure six indicators of spatial thinking skills, namely application, analysis, spatial interaction, representation, scale, and comprehensive. The data obtained were analyzed using the One Way ANOVA statistical test to determine the significant difference between the two groups. The results showed that the average posttest score of students in the experimental class was higher than that of the control class. In the experimental class, the average posttest score was 89, while in the control class it was 78. The highest score in the experimental class was 100, with the lowest score of 55. In contrast, the highest score in the control class was 94, with the lowest score of 50. The One Way ANOVA test showed a significant difference (p <0.05) between the two groups. Data analysis revealed that the use of Canva Site media in the PBL model made a positive contribution to improving students' spatial thinking skills, especially in indicators, spatial interaction analysis, and comprehensiveness. The conclusion of this study is that the application of the PBL model assisted by Canva Site media can increase student engagement in learning and help them understand spatial concepts more effectively than using PowerPoint media. Canva Site media offers streaming and interactivity that encourages students to think critically, creatively, and independently. This study recommends that teachers utilize Canva Site media not only in geography materials, but also in other subjects that require the development of spatial thinking skills. To achieve optimal results, thorough learning preparation is needed, including the preparation of open modules, media design, and training for teachers in using learning technology.
Entry oleh Arif 2026 Maret 16
Keywords: Problem-Based Learning; Canva Site; Spatial Thinking Skills; Quasi Experiments; Geography Education